Various Aspects Involved in the Study of Tooth Bleaching Procedure: A Questionnaire–Based Study - Mazilu Moldovan, Amalia; Popescu, Violeta; Ionescu, Corina Violeta; Cuc, Stanca; Craciun, Antarinia; Moldovan, Marioara; Dudea, Diana; Mesaros, Anca Stefania (International journal of environmental research and public health, 2022)
A beautiful smile is an important feature when it comes to a pleasant appearance of the face, and one of the most common situations that drive patients to book a dental appointment is tooth discoloration. Tooth bleaching is the treatment of choice for extrinsic tooth discoloration, as it is a cheap, fast, and minimally invasive procedure. This study aimed to provide comparative information on the perceptions of both patients and dentists regarding different whitening methods and on the factors involved in people’s willingness to recommend and use a bleaching procedure. In addition to this, this study evaluated the degree of satisfaction in relation to the bleaching methods and materials used; it also evaluated the following: negative side effects, economic characteristics and the patients’ perceptions of the aesthetic appearance of their dental arches, especially tooth color. The subjects that participated in the present study were selected based on their background and were then divided into two categories. The first group consisted of 120 patients who had received tooth-bleaching treatments in dental clinics during the study and the second group consisted of 127 dentists. A conventional sampling method was used. The study aimed to define a relationship between multiple aspects of the tooth-bleaching procedure, including the patients’ desires and their general knowledge of this procedure. Tooth color and the way it changes is a very important factor that motivates patients to come to the dentist for whitening procedures. Patients showed the highest levels of satisfaction with the results of in-office bleaching procedures. In the group consisting of dentists, satisfaction levels were higher for the procedure of home bleaching supervised by a dentist. Factors influencing the choice of bleaching materials are appreciated differently by dentists and patients. Furthermore, the rate of patients using OTC (over the counter) products was found to be high. Further research is needed to find more effective and safer alternatives to home tooth-bleaching procedures.